(untitled) - Brown, William H. (Orlando, Florida, 1998)
The book lays the foundation for studying organic chemistry covering the structures and typical reactions of the important classes of organic compounds: alkanes, alkenes, alkyl halides, alcohols, alkynes, ethers and epoxides, aldehydes and ketones, carboxylic acids and their derivatives, benzene and its derivatives, and finally amines. It also introduces the organic chemistry of the four major classes of biomolecules, namely carbohydrates, lipids, amino acids and proteins, and nucleic acids. Finally, the book discusses the organic chemistry of two key metabolic pathways, namely glycolysis and -oxidation of fatty acids
Keywords: Chemistry, organic